PENGUATAN USAHA MELALUI PENINGKATAN KAPASITAS SDM DAN PENGEMBANGAN STRATEGI PEMASARAN - Jati, Damar; Aziezy, Enrico (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to increase the capacity of human resources (HR) and develop a marketing strategy for the "Romansa Snack" Banana Chips Business in Karangcegak Village, Kutasari District, Purbalingga Regency. The method used is participatory mentoring, where business actors are actively involved in each stage of the activity. The results of the activity show that there is an understanding of business actors about the importance of good human resource management, such as workforce planning and employee performance evaluation. In terms of marketing, it focuses on optimizing the use of social media and e-commerce platforms to expand the market. Business actors are also expected to have a strategy for product diversification and packaging improvement to make it more attractive to consumers. The analysis of the business feasibility study shows that this business has bright prospects with positive financial indicators, such as Net Present Value (NPV) which is positive and Payback Period for 6 years and 4 months. Digital-based marketing strategies have a significant impact on increasing sales. In the future, it is hoped that business actors can continue to develop human resource skills and innovate in marketing so that their businesses can continue to grow and become one of the leading MSMEs in Purbalingga Regency.